PALESTINE AND JERUSALEM IN THE ISRAELI FRAMEWORK OF IRAN'S NATIONAL PRESS: KAYHAN CASE - Görgülü, Yusuf (Mehmet Akif KARA, 2020)
In this study, the representation of Israel with its contextual presentation to Jerusalem and Palestine in the national newspapers of Iran was emphasized. For this purpose, the frequency of contextual presentation regarding the discourses of Jerusalem and Palestine, how the messages for Jerusalem and Palestine were presented, and how the attitudinal practices against Israel were put forward. As a sample, Kayhan newspaper, which is acting under the guidance of Intelligence and the current regime in Iran, was chosen. In the current newspaper between 20.05.2020 and 27.05.2020, content analysis method and discourse analysis method were used for the purpose of representing the content presented for Jerusalem and Palestine in Israel. The research was carried out exclusively for Kayhan (Arabic) newspaper. The reason we limit our work to a narrow frame between these dates is that it is a date that marks the day of Jerusalem, and the expectation that the content production for Jerusalem and Palestine is high between these dates. The main reason for choosing Kayhan (Arabic) as a sample in our study is that the frequency of processing value / ideological data for Jerusalem, Palestine and the Middle East is evident.According to the results of the research, it was concluded that the Kayhan newspaper, acting under the guidance of the regime in Iran, offers content within the framework of the rhetoric's rhetoric, produces content for the political attitude / populist discourses of the regime and is in an effort to create public opinion with a similar view in reflecting the regime's perspective towards Israel.

Bu çalışmada, İran’ın ulusal gazetelerinde yer alan Kudüs ve Filistin’e yönelik içeriksel sunumu ile İsrail’in temsili üzerinde durulmuştur. Bu amaçla, Kudüs ve Filistin söylemlerine ilişkin içeriksel sunum sıklığı, Kudüs ve Filistin’e yönelik iletilerin ne şekilde sunulduğu ve karşısında yer alan İsrail’e ilişkin tutumsal pratiklerin ne şekilde ortaya konduğu üzerinde durulmuştur. Örneklem olarak İran’da İstihbarat ve mevcut rejimin güdümünde hareket eden Kayhan gazetesi seçilmiştir. 20.05.2020 ile 27.05.2020 arasında mevcut gazetede Kudüs ve Filistin’e yönelik sunulan içeriklerin İsrail özelinde temsili amacı ile içerik analizi ve söylem analizi yöntemi kullanılmıştır. Araştırma Kayhan (Arapça) gazetesi özelinde gerçekleştirilmiştir. Çalışmamızı bu tarihler arasında dar bir çerçevede sınırlandırmamızın sebebi, Kudüs gününe işaret eden bir tarih olması ve bu tarihler arasında Kudüs ve Filistin’e yönelik içerik üretim oranının yüksek olması beklentisidir. Ayrıca bu tarihlere yakın bir dönemde ABD’de George Floyd İsyanı başladığı için gazetenin ilgisinin ABD’deki isyanlara odaklanacağı düşüncesidir. Araştırmamızda örneklem olarak Kayhan (Arapça) seçilmesinin ana sebebi, Kudüs, Filistin ve Ortadoğu’ya yönelik değersel/ ideolojik verileri işleme sıklığının belirgin olmasıdır. Araştırma sonucuna göre, İran’da rejimin güdümünde hareket eden Kayhan gazetesi İktidarın söylemleri çerçevesinde içerikler sunduğu, rejimin politik tutumuna/popülist söylemlerine yönelik içerikleri ürettiği ve rejimin İsrail’e yönelik bakış açısını yansıtma noktasında benzer bir görünüm ile kamuoyu oluşturma çabası içerisinde olduğu sonucuna ulaşılmıştır.
İRAN ULUSAL BASININDA İSRAİL ÇERÇEVESİNDE FİLİSTİN VE KUDÜS: KAYHAN ÖRNEĞİ
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar